Chemical sensing with pulsed QC-DFB lasers operating at 15.6 μm - Kosterev, A. A.; Curl, R. F.; Tittel, F. K.; Rochat, Michel; Beck, Mattias; Hofstetter, Daniel; Faist, Jérôme (My University, 2002)
Pulsed thermoelectrically cooled QC-DFB lasers operating at 15.6 μm were characterized for spectroscopic gas sensing applications. A new method for wavelength scanning based on repetition rate modulation was developed. A non-wavelength-selective pyroelectric detector was incorporated in the sensor configuration giving the advantage of room-temperature operation and low cost. Absorption lines of CO2 and H2O were observed in ambient air, providing information about the concentration of these species.